(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Deaths due to coronary artery disease have been increasing in young people aged <40. Studies have reported an association between these deaths with hyperhomocysteinemia. The aim of this study was to compare serum homocysteine levels in middle-aged patients with coronary artery disease. This cross-sectional study was conducted among 52 cardiology inpatients of Bangabandhu Sheikh Mujib Medical University, Dhaka, from March 2021 to February 2022. Among them, 26 were young adults (<40 years, Group I), and 26 were middle-aged (≥40 years, Group II). Serum homocysteine was measured in all of them using an automated immunoassay analyzer. The younger patients had higher (P=0.001) median homocysteine (interquartile range) level, 13.5 (7.7 –28.4 mmol/L) compared to the middle-aged group, 10.0 (5.9 – 38.5 mmol/L). The hyperhomocysteinemia (>15 mmol/L) was 16.2% in Group I compared to 12.4% in Group II (P=0.001). Therefore, control measures for keeping homocysteine levels within the normal range in young people might be useful. BSMMU J 2022; 15(3): 197-200